Psychiatric Discourse, and the Social Negotiation of the Mentally Ill in Isan Locality - Pocapanishwong, Attama (Journal of Mekong Societies, 2013)
The objective of this article is to study insanity and the social being of the mentally ill in the midst of the negotiations between the discourse of medical science and that of the local health knowledge in Isan. This is related to the formulation of self or identity of the mentally ill, and also to the social negotiation between the mentally ill and the community. The conceptual framework is based on the concept of power-knowledge, subject, and discourse. The research found that the periphery of the meaning and the perception of mental illness has been dominated by the “psychiatric discourse” of medical science that shifts the local discourse (“phii baa”) to the dichotomy (“mad devil”) and makes the relational distinction between “the sane” / “the insane” (“khon dir / “khon baa”). Moreover, the practice of the mentally ill turns to use the institutional discipline that produces stigmatization. However, the mentally ill themselves have tactics to “play” with social definitions to resist and negotiate with the power and injustice that affect the social norms. Therefore, mental illness is always fluid and ambiguous, fluctuating between “insanity” and “sanity.”